Multiple Anterior Mitral Valve Perforation After Deep Transfemoral Aortic Valve Implantation - Fotbolcu,Hakan (2022)
Abstract Transcatheter aortic valve implantation (TAVI) is an alternative for high-risk aortic valve replacement. There are limited data related to the late complications of TAVI. Deep aortic prosthetic valve implantation can cause direct erosive perforation of anterior mitral leaflet or erosive endothelial lesion which predisposes the tissue to infective endocarditis. Our report emphasizes anterior mitral leaflet perforation after TAVI, which may be seen especially in patients exposed to sepsis.